Studi Terhadap Pemikiran Prof. Dr. Sadu Wasistiono, M.S. Mengenai Ilmu Pemerintahan Di Indonesia - Saputra, Danu Yanuar; Nurdin, Ismail; Sinaga, Jona Bungaran Basuki (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2025)
Throughout the history of a nation, reflections on governance often serve as a mirror of the spirit and direction of the civilization it aspires to achieve. This thesis explores the intellectual contributions of Prof. Sadu Wasistiono Wasistiono, a scholar who, in the twilight of his academic career, has significantly influenced the theoretical foundations and practical discourse of governance in Indonesia. This research employs a descriptive methodology with a qualitative approach. Data collection methods include field research— comprising observations, interviews, and documentation—and library research through literature review. The data is analyzed using techniques such as data reduction, data display,and conclusion drawing with verification. The findings reveal that Prof. Sadu Wasistiono Wasistiono's thoughts significantly contribute to the development of governance studies and remain highly relevant in addressing contemporary governance challenges. However, the research identifies several critical issues: the limited availability of theories, concepts, and models in governance studies; a persistent egotism among intellectual elits in articulating their viewpoints; and inadequate incentives and visibility for research and publications in Indonesia compared to countries like the United States and Japan. The study underscores the urgency of fostering a spirit of collaboration among intellectual elits and between academics and government stakeholders. Such collaboration is essential for developing governance theories rooted in local contexts yet aligned with international standards. Furthermore, the study advocates for increased incentives for research and publication, alongside the adoption of best practices from other countries, to enhance governance standards and contribute to national and global progress.